Hvordan lyder det når man er fuld? En fonologisk analyse af alkoholiseret tale i Curlingklubbens Julefrokost og Bjorholms Corner Julekalender. - Bloch, Karoline; Andersen, Dennis (Journal of Language Works - Sprogvidenskabeligt Studentertidsskrift, 2023)
This article presents a suggestion for how to ethically examine changes in speech production caused by alcohol consumption. Specifically, the study examines palatalizations of consonants in speech in two different settings: One in the setting of a podcast Christmas party and the other of social media hosts who each drink 24 beers. We have been able to describe the phonological and auditory features of palatalization and also measure the increase of palatalization in speech from increasingly drunk speakers. We have used Curlingklubben’s podcast for a qualitative analysis. We have found that under the influence of alcohol the tongue control is diminished, and we suggest that it is therefore more likely to produce palatalization. We have used Bjorholms Corner Julekalender for a quantitative study from which we found that the increase in palatalization has some correspondence with intake of alcohol in one speaker and that /l/ /g/ /k/ and /t/ were the phonemes most affected. This article contributes to our understanding of the influence that alcohol has on human speech using publicly available recordings of drunk speakers.